2009
DOI: 10.1007/s11920-009-0058-1
|View full text |Cite
|
Sign up to set email alerts
|

Gene-environment interactions in attention-deficit/hyperactivity disorder

Abstract: Attention-deficit/hyperactivity disorder (ADHD) is a heterogeneous disorder characterized by inattention, impulsivity, and/or hyperactivity in children and adults. Putative environmental risk factors for ADHD include toxin and prenatal smoke exposure, low socioeconomic status, and parental marital instability and discord. Genetic associations with ADHD have been found in the dopaminergic, serotonergic, and noradrenergic neurotransmitter systems, but findings are inconsistent across studies. Herein, we review s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
33
0
3

Year Published

2010
2010
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 50 publications
(37 citation statements)
references
References 32 publications
1
33
0
3
Order By: Relevance
“…In contrast, five articles, in agreement with the present scientific consensus (Ficks & Waldman, 2009; Li et al, 2014; Sonuga-Barke, 2010), challenged this claim. For example we found in Le Figaro (19 February 2004): “It is obvious that hyperactive children suffering from attention deficit are increasingly numerous.…”
Section: Resultsmentioning
confidence: 73%
See 1 more Smart Citation
“…In contrast, five articles, in agreement with the present scientific consensus (Ficks & Waldman, 2009; Li et al, 2014; Sonuga-Barke, 2010), challenged this claim. For example we found in Le Figaro (19 February 2004): “It is obvious that hyperactive children suffering from attention deficit are increasingly numerous.…”
Section: Resultsmentioning
confidence: 73%
“…We tested whether and how they reported on three scientific questions about ADHD: (i) whether ADHD is mainly genetic in origin; (ii) whether methylphenidate treatment decreases the risk of academic underachievement; and (iii) whether brain imaging techniques are able to reveal ADHD in individual patients. Scientific studies demonstrated that genetic factors only mildly contribute to ADHD etiology whereas environmental factors play a central role (Ficks & Waldman, 2009; Sonuga-Barke, 2010). In a recent review of more than 300 molecular genetic studies (Li, Chang, Zhang, Gao, & Wang, 2014, p. 19), the authors concluded: “current findings from genetic studies of ADHD are still inconsistent and inconclusive.…”
Section: Introductionmentioning
confidence: 99%
“…These treatment modalities have flowed, in part, from research examining the etiology of ADHD and ADHD symptomatologies. Most of the extant research has indicated that ADHD is a complex multifactorial phenotype that is influenced in large part by genetic factors and even gene-environment interactions [5,7,14,[32][33][34][35][36][37][38][39][40]. The current study added to the existing body of research by examining whether genetic liabilities for criminality and alcoholism affected ADHD symptoms in a sample of American adoptees.…”
Section: Discussionmentioning
confidence: 93%
“…As a result, it was not possible to separate the effects of having an alcoholic or criminal biological parent from the effects of having an ADHD biological parent. Third, there is some evidence that exposure to toxins either in utero or very early in life may be related to the development of ADHD [32,34,37,41]. Given that parents with ADHD and criminal parents are at risk for financial problems and living in disadvantaged environments [42][43][44][45], it is possible that the connection between genetic risk and ADHD is mediated through disadvantaged environments.…”
Section: Discussionmentioning
confidence: 99%
“…For instance, it may be that the problems with the dopaminergic system that are related to ADHD and smoking are also linked to some of the cognitive deficits (e.g., cognitive coping) or social factors (e.g., parental smoking) which are associated with ADHD and smoking. Studies on gene-environment interactions and general ADHD symptomology suggest that there may be interactions between these dopaminergic genes and prenatal risk factors (e.g., maternal smoking during pregnancy) which increase a child's risk for ADHD (Ficks and Waldman 2009;Plomp et al 2009). While the literature on gene-environment interactions and ADHD is just emerging as an important area of research, similar studies could examine these interactions related to cigarette smoking and ADHD.…”
Section: Summary Of Literature Reviewmentioning
confidence: 99%